An Islamic approach to poetics: the role of Muslim philosophers in offering an alternative literary theory - Nusrat, Zubaida; Abdul Rahim, Adibah (UNIVERSITI KEBANGSAAN MALAYSIA (UKM), 2025)
Little is known about the contributions made by the Muslim literary philosophers of the medieval age since their ideas on poetics have not been well documented. Al-Farabi and Ibn-Sina, offered an explanation of reasoning to reconcile poetry with the corpus of consistent ideas regarding truths as revealed in the Quran. Ibn Rushd compared poetry to a logical organ of philosophy, claiming that its distinctive characteristics enable the communication of truth and draw the creative mind nearer to God. Despite their extensive theoretical resources in poetry, the literary philosophies of these thinkers are largely unknown to Muslims and non-Muslims alike. In addition, there are some amounts of confusion and ambivalence about the distinctiveness of their literary theories and has much misunderstanding regarding the importance of faith and logic, as revealed in their exposition of poetic language, imagination, syllogism, nature of the subject, aesthetics and moral validity. Therefore, this paper sheds light on the tradition of poetics in both pre-Islamic Arab culture and medieval Arabic-Islamic period, discusses the reasons for the acceptance of Aristotle’s Poetics within the Muslim community and explores the distinctive aspects of the leading Muslim philosophers’ literary theories that make them more advanced, and dynamic compared to the Greeks.